2019
DOI: 10.1186/s40621-019-0194-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of high school athletic trainer services on medical payments and utilizations: a microsimulation analysis on medical claims

Abstract: Background Increasing athletic trainer (AT) services in high schools has attracted widespread interest across the nation as an effective instrument to manage injuries and improve children’s health, but there is a lack of evidence on potential medical savings. Our study aimed to address this knowledge gap and provide evidence of AT impacts on medical payments and utilizations to inform public policy decision. Methods We obtained medical claims of patients aged 14 to 18 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…The observed differences in access among school SES may lead to a variety of consequences that disproportionately affect lower SES communities. These observed differences may include: increased health care costs to the community atlarge and/or the athlete's family; secondary to unnecessary emergency department visits [25][26][27] and subsequent services, 28,29 ; inappropriate referrals 25,30 and lost productivity from missed days of work and school. 31 Further, athletes from lower SES communities may be more at risk of injury mismanagement 32 (in particular concussion injury) 13 as well as decreased availability of the AT to provide evaluative, 25 rehabilitative, 18 and preventative services 26 to athletes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed differences in access among school SES may lead to a variety of consequences that disproportionately affect lower SES communities. These observed differences may include: increased health care costs to the community atlarge and/or the athlete's family; secondary to unnecessary emergency department visits [25][26][27] and subsequent services, 28,29 ; inappropriate referrals 25,30 and lost productivity from missed days of work and school. 31 Further, athletes from lower SES communities may be more at risk of injury mismanagement 32 (in particular concussion injury) 13 as well as decreased availability of the AT to provide evaluative, 25 rehabilitative, 18 and preventative services 26 to athletes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to rehabilitative care, athletic training presence has also been credited as playing a central role in decreasing sport injury presentation for acute injury management in higher-cost clinical settings such as emergency departments. 25,26,30 Lateral ankle sprains alone, which are commonly managed by ATs, 34 were shown to incur emergency room charges ranging from $702-$1408 in 2010. 27 These charges are not only an undue burden for society at-large, but also for individual athlete families, and potentially more so for athletes from lower SES communities.…”
Section: Discussionmentioning
confidence: 99%
“…30 After looking at the medical need, a cost-benefit analysis would demonstrate the economic benefit of athletic training services. 31 One study found that athletic trainers reduce emergency visits 10 which cost an average of $2,032 per visit. 32 Two-thirds of hospital emergency visits annually are avoidable which has the potential to save $32 billion dollars per year.…”
Section: Discussionmentioning
confidence: 99%
“…8 Previous studies have shown that access to an athletic trainer in the secondary school setting positively influences the reported incidence of sports-related concussions and post-concussion management activities, O n l i n e F i r s t reduces emergency room visits and cardiac-related deaths, provides preventative medicine services, and increases patient access to care. [9][10][11][12][13] One reason for this being high school athletic trainers are often not reimbursed through a third party, which gives access to a wider variety of SES groups. 13 Further, at the local practice level, there are several steps that athletic trainers can implement to provide better patient-centered care to these underserved populations, which can increase access to care.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%
“…Primary care skills in athletic settings have previously been recognized for the reduction of emergency room visits through statistical modeling and claims data analysis. (Li et al, 2019) This expansion of traditional AT practices to new settings has proven valuable in providing a screening mechanism to protect the patient and the facility while at the same time triaging care needs for musculoskeletal conditions have allowed the facilities to safely continue providing essential services. The shift from the traditional value of revenue generation to upstream triage and clinical care coordination has allowed ATs in outpatient rehabilitation facilities to be directly involved in administrative and clinical operations at a level significantly impacting patient care and practice viability.…”
Section: Case: Telemedicine For Patient Onboarding and Musculoskeletamentioning
confidence: 99%